2019
DOI: 10.1016/j.rmcr.2019.100886
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly progressive interstitial lung disease due to anti-melanoma differentiation associated protein-5 requiring a bilateral lung transplant, and complicated by kennel cough

Abstract: The association between inflammatory myopathies anti-synthetase syndrome and interstitial lung disease has been recognized since the 1950s. Patients generally present with gradual onset of symptoms and slow progression of fibrosis over months to years. Herein, we describe a previously well 51-year-old man who presented with three months of progressive small joint arthritis, cough, dyspnea, and eventually hypoxemic respiratory failure following a viral prodrome. He continued to decompensate despite high dose co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Shoji et al reported the case of a female patient with a rapidly progressive ILD associated with anti-MDA-5 antibodies that underwent successful lung transplantation after an intensive immunosuppressive therapy including cyclophosphamide and intravenous immunoglobulins (17). Other similar cases have been reported since then, with favorable outcomes (18,19). Like our two patients, at least one of them had anti-SSA 52 antibodies (18), which are frequently associated with anti-MDA5 antibodies (10) and seem to be correlated with severe forms of ILD (2,20).…”
Section: Discussionmentioning
confidence: 98%
“…Shoji et al reported the case of a female patient with a rapidly progressive ILD associated with anti-MDA-5 antibodies that underwent successful lung transplantation after an intensive immunosuppressive therapy including cyclophosphamide and intravenous immunoglobulins (17). Other similar cases have been reported since then, with favorable outcomes (18,19). Like our two patients, at least one of them had anti-SSA 52 antibodies (18), which are frequently associated with anti-MDA5 antibodies (10) and seem to be correlated with severe forms of ILD (2,20).…”
Section: Discussionmentioning
confidence: 98%
“…RP-ILD was mainly defined as progressive dyspnea, or according to HRCT findings secondary to ILD within 3 months after the onset of respiratory symptoms (9, 10). RP-ILD often occurs as a complication of CADM, which usually portends poor prognosis with reported mortality rates in the first year as high as 60% (11). Anti-MDA5 antibodies were first identified by Sato et al in 2005 in Japanese patients with CADM (12).…”
Section: Discussionmentioning
confidence: 99%
“…There is an additional experience of lung transplants reported by other authors [ 67 , 68 , 69 •, 70 , 74 ] including a total of 7 patients, all of them survived. Thus, lung transplantation is a viable therapeutic option in refractory patients with anti-MDA5-associated RP-ILD.…”
Section: How To Identify the Best Therapeutic Strategy?mentioning
confidence: 96%
“…Thus, it applies to anti-MDA5-positive CADM-associated RP-ILD patients refractory to combined immunosuppressive therapy, mostly as a bridge to a most definitive solution like lung transplantation or while waiting for a response to the immunosuppressive drugs. Currently, there is scarce data on the efficacy of VV-ECMO in this type of patients [ 61 , 62 •, 63 68 , 69 •, 70 ], and was considered successful only in a few patients, either because it helped to improve the clinical status of the patient or it allowed performing a lung transplantation [ 67 , 68 , 69 •, 70 ].…”
Section: How To Identify the Best Therapeutic Strategy?mentioning
confidence: 99%